"Second Chances" for Adolescent Mothers: Four Decades of Insights and Lessons on Effectiveness and Scale-up of Jamaica's PAM. Issue 2 (3rd April 2023) - Amo-Adjei, Joshua; Caffe, Sonja; Simpson, Zoe; Harris, Michelle; Chandra-Mouli, Venkatraman
Abstract: The Women's Center of Jamaica Foundation's (WCJF) Programme for Adolescent Mothers)—has supported pregnant girls and adolescent mothers to have uninterrupted access to education and allied services since 1978. This paper analyzes the conception, establishment, scale up and sustainability of the Programme. The Programme evolved from a small, local initiative into a national and international model. Repeat pregnancy has remained under 2% among programme beneficiaries since inception. While the core package of interventions has remained for the past 40 years, some new dimensions have been added, with the most recent one being support for transition to higher education, all of which are aimed at strengthening the impact of the Programme. The achievements of the Programme were propelled prominently by a progressive national policy environment with the support of several non-state actors. The PAM demonstrates the value of sustained cross-sectoral support, spearheaded, or fully supported by the state in providing opportunities for adolescent mothers.